2018
DOI: 10.1093/bioinformatics/bty278
|View full text |Cite
|
Sign up to set email alerts
|

Protein threading using residue co-variation and deep learning

Abstract: MotivationTemplate-based modeling, including homology modeling and protein threading, is a popular method for protein 3D structure prediction. However, alignment generation and template selection for protein sequences without close templates remain very challenging.ResultsWe present a new method called DeepThreader to improve protein threading, including both alignment generation and template selection, by making use of deep learning (DL) and residue co-variation information. Our method first employs DL to pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
97
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(101 citation statements)
references
References 41 publications
3
97
0
Order By: Relevance
“…Moreover, 50% of the time RaptorX‐TBM finds the correct fold that is 10% more than that of our work (considering 20 full‐length targets). It should be noted here that RaptorX‐TBM uses inter‐residue distance maps that is considered more informative than inter‐residue contact maps in predicting protein 3D structure . Moreover, the comparison of our work with RaptorX‐TBM may not be fair since threading performance is directly dependent on the template library and RaptorX‐TBM potentially is based on a different template library compared to our work.…”
Section: Resultsmentioning
confidence: 88%
“…Moreover, 50% of the time RaptorX‐TBM finds the correct fold that is 10% more than that of our work (considering 20 full‐length targets). It should be noted here that RaptorX‐TBM uses inter‐residue distance maps that is considered more informative than inter‐residue contact maps in predicting protein 3D structure . Moreover, the comparison of our work with RaptorX‐TBM may not be fair since threading performance is directly dependent on the template library and RaptorX‐TBM potentially is based on a different template library compared to our work.…”
Section: Resultsmentioning
confidence: 88%
“…CAMEO evaluates the structure predictions applying different scores for assessing different aspects of modeling, such as accuracy of a single protein chain, the homo‐oligomeric interface, or the binding site (Table ). Here, we categorized the data into the target domains “hard,” “medium,” and “easy.” The three best methods “Robetta,” “Raptor‐X,” and “IntFOLD5‐TS returned all hard targets (in total 62) with a very similar performance, both in average lDDT and SD, of 47.29±12.96, 45.25±13.57, and 44.79±12.82 (CAD‐scores: 0.55±0.09, 0.53±0.10, and 0.52±0.09), respectively. Although the performance is very similar on this specific target set, the response times vary greatly with “Raptor‐X” clearly in the lead (7.8 hours).…”
Section: Resultsmentioning
confidence: 97%
“…Here, we categorized the data into the target domains "hard," "medium," and "easy." The three best methods "Robetta," 19 "Raptor-X," 20 CAMEO analyses the accuracy of the binding-site residues ("lDDT-BS" 4 ), where on the current data set across 94 targets and 83 unique ligands (see Data S1), the top modeling groups are also producing good quality binding sites with lDDT-BS scores close to 70.…”
Section: General Performance Analysismentioning
confidence: 99%
“…In contrast, deep ResNet not only works very well on proteins without many sequence homologs, but also can directly predict interresidue or interatom distance. 8,9 In CASP12 and previous CAMEO tests we have demonstrated that deep ResNet can greatly improve contact prediction 6,10-12 and that without extensive conformation sampling, contacts predicted by deep ResNet can be used to build correct folds for (even membrane) proteins without detectable homology in PDB. 13 Afterwards, the power of deep convolutional neural network has been further validated by other research groups who have developed similar deep networks for contact prediction.…”
Section: Introductionmentioning
confidence: 93%
“…Prior to CASP13, we have extended our deep ResNet to protein distance prediction and showed that distance-based potential predicted by ResNet may significantly improve protein threading for targets without good templates in PDB. 8 We have developed a simple and efficient distance geometry algorithm that may quickly fold a protein sequence from distance and torsion angles predicted by deep ResNet. 9 Our deep ResNet not only can predict distance matrix from sequence and coevolutionary information, but also from template and alignment information.…”
Section: Introductionmentioning
confidence: 99%